Conserved Golgi nucleoside diphosphatases drive protein glycosylation and virulence in Fusarium graminearum - Shin, Soobin; Choi, Yejin; Phan, Thuy Thi Thanh; Song, Seonwoo; Lee, Nahyun; Park, Jiyeun; Kim, Sieun; Jeon, Hosung; Kim, Jung-Eun; Min, Kyunghun; Kim, Hun; Choi, Gyung Ja; et al. (BMC, 2026)
The Golgi apparatus orchestrates post-translational modification and vesicular trafficking, with guanosine diphosphatases (GDPases) facilitating nucleotide-sugar transport by hydrolyzing guanosine diphosphate (GDP) to guanosine monophosphate (GMP). Although GDPase functions are well known in yeast and human-pathogenic fungi, their roles in filamentous fungi, including plant pathogens, remain largely unexplored. Here, we investigated the biological functions of the Golgi GDPases Gda1 and Ynd1 in the wheat head blight pathogen Fusarium graminearum. While loss of FgYND1 only resulted in minor growth problems, deletion of FgGDA1 caused pleiotropic deficiencies in mycelial development, conidiation, sexual reproduction, and virulence. Notably, FgYND1 overexpression partially rescued the defects of the FgGDA1 deletion mutant in the developmental and invasive processes, indicating overlapping yet non-equivalent functions. Glycoproteomics analysis revealed global remodeling of glycoprotein profiles in the FgGDA1 deletion mutant, with prominent changes among enzymes in carbon metabolism, consistent with disrupted Golgi-dependent glycosylation. According to our results, FgGda1 is the primary driver of protein glycosylation-dependent fungal development and virulence in F. graminearum, with FgYnd1 providing only partial redundancy.